Case Report: Paraneoplastic Tumefactive Demyelination Associated With Seminoma - Shiraishi, Wataru; Umemura, Takeru; Nakayama, Yuuki; Yamada, Yui; Shijo, Masahiro; Hashimoto, Tetsuya (Frontiers in Neurology, 2022)
Paraneoplastic tumefactive demyelination (TD) is a rare disorder of the central nervous system that can be challenging to diagnose. Here, we describe a 32-year-old Japanese man with a TD associated with testicular seminoma. He presented with symptoms of right-sided motor and sensory impairment 2 days after vaccination for coronavirus disease 2019 (COVID-19). Brain magnetic resonance imaging (MRI) showed a high-intensity lesion in the left internal capsule. He had a 3-year history of enlargement of the left testicle. Blood examination showed tumor marker elevation and the presence of anti-amphiphysin antibodies. Whole-body computed tomography (CT) revealed mass lesions in the left testicle and enlargement of the retroperitoneal lymph nodes. Radical orchiectomy was performed. As the pathology showed testicular seminoma, chemotherapy was administered. After surgery, his neurological symptoms deteriorated. MRI revealed that the brain lesion had enlarged and progressed to a tumefactive lesion without gadolinium enhancement. The cerebrospinal fluid (CSF) examination was normal without pleocytosis or protein elevation. Steroid pulse therapy was added; however, his symptoms did not improve. A brain stereotactic biopsy was performed and the sample showed demyelinating lesions without malignant cells. As the initial corticosteroid therapy was ineffective, gamma globulin therapy was administered in parallel with chemotherapy, and the clinical symptoms and imaging findings were partially ameliorated. TD seldom appears as a paraneoplastic neurological syndrome. In addition, there are few reports of COVID-19 vaccination-associated demyelinating disease. Clinicians should recognize paraneoplastic TD, and the further accumulation of similar cases is needed.